Trends in concentrations and export of nitrogen in boreal forest streams - Sarkkola, Sakari; Nieminen, Mika; Koivusalo, Harri; Laurén, Ari; Kortelainen, Pirkko; Mattsson, Tuija; Palviainen, Marjo; Piirainen, Sirpa; Starr, Mike; Finér, Leena (Finnish Environment Institute, 2016)
Peer reviewed